The genus Tocantinia (Amaryllidaceae, Amaryllidoideae) and two new species from Brazil - Büneker, Henrique Mallmann; Bastian, Regis Eduardo; Soares, Kelen Pureza; Costa, Calmito Miranda (Balduinia, 2016)
A synopsis of the genus Tocantinia is provided, with two new species being described and illustrated: T. dutilhiana and T. stigmovittata. Descriptions, illustrations and data on etymology, ecology, conservation status, distribution and habitat of the species are provided. The taxonomic placement of the genus in morphological and phylogenetic aspects is discussed.